Radium-223 in combination with docetaxel in patients with castration-resistant prostate cancer and bone metastases: a phase 1 dose escalation/randomised phase 2a trial. (June 2019) - Morris, Michael J.; Loriot, Yohann; Sweeney, Christopher J.; Fizazi, Karim; Ryan, Charles J.; Shevrin, Daniel H.; Antonarakis, Emmanuel S.; Pandit-Taskar, Neeta; Deandreis, Désirée; Jacene, Heather A.; Vesselle, Hubert; Petrenciuc, Oana; et al.
Abstract: Purpose: Radium 223 dichloride (radium-223) is an alpha particle–emitting bone-directed therapy that prolongs overall survival in men with bone-predominant metastatic castration-resistant prostate cancer (mCRPC). Docetaxel is an antimicrotubule cytotoxic agent that improves survival in mCRPC. We investigated whether combining these potentially cross-sensitising agents to dually target tumour and bone would be safe and effective. Patients and methods: Phase 1 was a dose escalation study to define a recommended phase 2 dose (RP2D) of docetaxel and radium-223. In phase 2a, patients were randomised 2:1 to the recommended combination regimen or docetaxel at a dose of 75 mg/m 2 every 3 weeks (q3w). Patients with bone-predominant mCRPC were eligible. End-points were safety, efficacy and treatment-related changes in serum and imaging biomarkers. Results: Twenty patients were enrolled in phase 1; 53 patients were randomised in phase 2a: 36 to combination treatment and 17 to docetaxel alone. The RP2D for the combination was radium-223 55 kBq/kg every six weeks × 5 doses, plus docetaxel 60 mg/m 2 q3w × 10 doses. Febrile neutropenia was dose limiting. A higher rate of febrile neutropenia was seen in the docetaxel monotherapy arm (15% vs 0%); the safety profile of the treatment groups was otherwise similar. The combination arm had more durable suppression of prostate-specific antigen (median time to progression, 6.6 vs 4.8 months, respectively), alkaline phosphatase (9 vs 7 months) and osteoblastic bone deposition markers. Conclusions: Radium-223 in combination with docetaxel at the RP2D was well tolerated. Exploratory efficacy data suggested enhanced antitumour activity for the combination relative to docetaxel alone. Comparative studies with end-points of clinical benefit are warranted. ClinicalTrials.gov number: NCT01106352. Highlights: Radium-223 55 kBq/kg every six weeks × 5 and docetaxel 60 mg/m 2 every three weeks (q3w) × 10 were recommended in phase 1. Combination was well tolerated in the randomised phase 2a part of the study. Combination presented no more safety concerns than docetaxel alone at a dose of 75 mg/m 2 q3w. Exploratory efficacy data suggested enhanced antitumour activity for the combination therapy.